2016
DOI: 10.1093/ntr/ntw227
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Purchasing Patterns, Readiness to Quit, and Quit Attempts Among Homeless Smokers

Abstract: Adults who are homeless smoke at greater rates and quit at lower rates than domiciled adults, leading to significant smoking-related health disparities among this group. Findings suggest that cigarette purchasing patterns are linked with readiness to quit smoking among smokers who are homeless. Results elucidate one of the myriad factors that contribute to tobacco-related disparities among this group and findings may have implications for cessation interventions in homeless shelters and other contexts where re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Limitations of this study include the use of an adult homeless sample from one city, which may limit the generalizability of results to other cities or states, particularly with different tobacco product pricing/ taxation and access to various CU products that might affect use patterns and motives (Wrighting et al, 2016). A report from the Oklahoma City Planning Department indicates that in January 2016, there were approximately 1511 homeless adults in Oklahoma City (Oklahoma City Planning Department, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study include the use of an adult homeless sample from one city, which may limit the generalizability of results to other cities or states, particularly with different tobacco product pricing/ taxation and access to various CU products that might affect use patterns and motives (Wrighting et al, 2016). A report from the Oklahoma City Planning Department indicates that in January 2016, there were approximately 1511 homeless adults in Oklahoma City (Oklahoma City Planning Department, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Study limitations include the use of an adult homeless convenience sample from a single city in Oklahoma, which may limit the generalizability of results to homeless adults more broadly or to those in other cities. 50 Additionally, a smaller proportion of women in the study were alcohol users relative to men (35.6% vs. 51.4% respectively); though a power analysis concluded sufficient power (> 80%) for resulting conclusions for both the entire sample and alcohol users-only sample based on the statistical analyses being conducted. According to an Oklahoma City Planning report, there were approximately 1,511 homeless adults in Oklahoma City at a point-in-time in January 2016, 51 suggesting that our sample comprised roughly 40% of that city’s homeless population.…”
Section: Discussionmentioning
confidence: 89%
“…The primary goal of PSH is to ensure housing stability. Previous studies have shown that cigarette smoking can contribute to up to a third of monthly expenditures, representing a substantial financial burden in a population with limited resources (Baggett et al, 2016; Wrighting, Businelle, Kendzor, LeBlanc, & Reitzel, 2017). Staff reported that while they acknowledged the financial burden of smoking among clientele, no staff addressed smoking in the context of financial management.…”
Section: Discussionmentioning
confidence: 99%